Ritual landscape and performance : proceedings of the international conference on ritual landscape and performance, Yale University, September 23-24, 2016 - Geisen, Christina, (Yale Egyptological studies ;, 2020)
""Ritual Landscape and Performance" contains the Egyptological contributions from the homonymous conference held at the Department of Near and Middle Eastern Civilizations of Yale University on September 23-24, 2016. The various articles discuss the use of ritual landscape from the Old to the New Kingdom of Ancient Egypt, by focusing on landscape archaeology of specific sites such as Saqqara, el-Bersheh, Abydos, Thebes, as well as Aniba in Nubia. Further contributions elucidate the interaction of desert and the Nile Valley through rock art, the depictions of watery environments in the delta and their association to rituals, as well as the habitation of landscapes using the example of southern Middle Egypt"--